Methane route of hydrocarbons formation at very high pressure and high temperature. - V. G. Kutcherov; A. Yu. Kolesnikov (Тонкие химические технологии)
Results of experimental investigations of synthesis of hydrocarbon systems at high pressure and different mechanisms of synthesis are discussed. experimental results presented in this paper confirm the possibility of synthesis of hydrocarbon at mantle conditions from methane. these results can be accepted as support for the theory of the abyssal abiotic petroleum origin.